Analisis Struktural dan Tema dalam Naskah Drama Karya Eugene Ionesco Terjemahan W.S. Rendra - Adinda Intan Mulya Prayetno; Agung Danuarta; Anisa Putri; Arum Fajar Rahmawati; Arvirelia Rahmatillah; Herlinda Herlinda (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Drama, as a form of literary work, plays a significant role in reflecting life values, social issues, and the psychological dynamics of human beings. Kakek dan Nenek (Grandfather and Grandmother), a play by Danarto, is a literary piece rich in philosophical and emotional meaning, portraying the complexity of human relationships, especially in old age. The background of this research is based on the importance of understanding the aesthetic, symbolic, and humanitarian messages embedded in dramatic works, particularly in the social and spiritual lives of the characters. The objective of this study is to analyze the structure, theme, characters, and symbols used in the play KAKEK dan NENEK, as well as to uncover the life values it conveys. This research employs a descriptive qualitative method with structural and semiotic approaches, where the data are derived from the original script and analyzed both textually and contextually. The findings reveal that the play not only illustrates the eternal love story between the two main characters but also implies social criticism, existential reflection, and the use of symbols such as a rose stem, a clock, and the sound of a baby to represent the life cycle, hope, and mortality. The dynamic, poetic, and emotionally rich dialogue structure enhances the reader's and viewer's experience in comprehending deeper meanings of life. Overall, the analysis shows that this play is a work of profound meaning, linguistic aesthetics, and strong narrative power.